2021
DOI: 10.1002/agj2.20753
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application uniconazole enhanced lodging resistance of hybrid indica rice by altering basal stem quality under poor light stress

Abstract: Poor light stress causes lodging risks in hybrid indica rice (Oryza sativa L.) in Sichuan Basin, China. However, the effective way of improving lodging resistance of hybrid indica rice by plant regulation strategy under poor light stress has not yet been investigated. A 2‐yr field study, comparing the three foliar application uniconazole rates under normal light and shading condition, was conducted to determine the lodging resistance and its physiological mechanism by using two hybrid rice varieties (Yuxiang20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…The lodging and bending caused by insufficient stem strength seriously affect the yield and quality of plants, and reduce their commercial value. The thickening and development of the secondary cell wall provides stronger mechanical support for plant stems (Shah et al., 2019; Zhang, Yao, et al., 2022; Zhong et al., 2019). Thus, understanding the transcriptional regulatory network of secondary cell wall thickening and development in is crucial for lodging or bending resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lodging and bending caused by insufficient stem strength seriously affect the yield and quality of plants, and reduce their commercial value. The thickening and development of the secondary cell wall provides stronger mechanical support for plant stems (Shah et al., 2019; Zhang, Yao, et al., 2022; Zhong et al., 2019). Thus, understanding the transcriptional regulatory network of secondary cell wall thickening and development in is crucial for lodging or bending resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that secondary cell walls also provide mechanical strength for structural support. Stem strength was significantly positively correlated with stem secondary wall thickness in crops such as rice ( Oryza sativa ; Zhang, Yao, et al., 2022) and wheat ( Triticum aestivum ; Khan et al., 2020), and in ornamental plants such as herbaceous peony ( Paeonia lactiflora Pall. ; Zhao, Shi, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because lodging can result in lower grain yields, reduced grain quality, more difficult mechanical harvesting, lower harvest efficiency, and increasing production costs, it is one of the most important factors influencing DSR grain yield potential [2][3][4]. Previous studies have shown that lodging can be caused by many internal and external factors, including rice variety, wind, rain, planting patterns, seeding rates, N fertilization approach, light, any phytohormones [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, N fertilization recommendations for DSR focus on fertilizer type; the fertilizer rate or ratio, especially coupled with SR, is less well-researched. Additionally, excessive N application not only causes serious environmental problems such as soil acidification and water eutrophication [16,17], but also increases crop lodging risk [5][6][7][8]10]. Farmers employing a DSR approach often combine high SR with high N fertilization rates, both of which result in higher lodging risk.…”
Section: Introductionmentioning
confidence: 99%